A Qualitative Study on the Implementation of the Total Physical Response (TPR) Method in Enhancing Students’ Speaking Ability in Narrative Texts - Firman Daris Laia; Nurhalimah; Fatin Nadifa Tarigan (LingPoet: Journal of Linguistics and Literary Research, 2026)
Speaking is an essential skill in language learning that enables students to communicate ideas, express opinions, and engage in meaningful interactions. However, many students still experience difficulties in speaking English, particularly in terms of fluency, pronunciation, and confidence. Preliminary observation showed that only 6 out of 28 students (21%) were able to respond to questions in English without using translation tools, indicating a low level of speaking proficiency. This study aims to explore the use of the Total Physical Response (TPR) method in improving students’ speaking skills in narrative texts. This research employed a qualitative descriptive approach to gain an in-depth understanding of students’ learning experiences during the implementation of TPR. The data were collected through classroom observations and interviews, focusing on students’ participation, fluency, pronunciation, and comprehension of narrative texts. The findings revealed that the implementation of the TPR method increased students’ engagement, with approximately 75% of students actively participating in speaking activities. In addition, students showed improvement in confidence, pronunciation accuracy, and fluency. The TPR method also helped reduce students’ anxiety when speaking English. Therefore, TPR is considered an effective teaching strategy for improving students’ speaking skills.